Cogan’s syndrome – A case series - Glišić, Branislava; Stević–Carević, Silvija; Ristić, Gorica; Dedović, Jelena (Vojnosanitetski pregled, 2021)
Introduction. Cogan’s syndrome is a rare variable vessel vasculitis. It can be typical and atypical. Basis of the treatment comprises glucocorticoids, and in patients with systemic manifestations, immunosuppressive drugs. Case report. We wanted to present the experience of the Clinic for Rheumatology and Clinical Immunology of the Military Medical Academy, Belgrade, in diagnosing and treating patients suffering from Cogan’s syndrome. The analysis included 7 patients. Patients’ demographic characteristics, disease manifestations, course of the disease, applied treatment and treatment outcome were analysed. Five of the patients were women and 2 were men, with the average age of 39 ± 13 (25–65) years. The typical form of the disease manifested in 1 patient. In 6 patients, the first manifestation was the audiovestibular dysfunction. In 1 patient, systemic manifestations were the first to appear. In the cases where the disease manifested atypically, 3 patients developed conjunctivitis, 2 episcleritis, and 1 uveitis. They all had systemic manifestations. One female patient was diagnosed with aortitis and aortic insufficiency. They all tested positive for inflammatory biohumoral syndrome. Four patients had positive antinuclear antibodies, 3 anticytoplasmic antibodies, and 1 positive rheumatoid factor. They were all treated with glucocorticoid and immunosuppressive drugs. Methotrexate was administered to all the patients in doses up to 20 mg per week. Pulses of cyclophosphamide were administered to 2 female patients. All patients went successfully into remission. The female patient with the typical form of the disease experienced permanent bilateral hearing loss. Conclusion. Patients with a rapidly developed audiovestibular dysfunction should be viewed as suffering from Cogan’s syndrome from the viewpoint of differential diagnosis. A timely treatment with glucocorticoids can prevent hearing loss and the development of systemic manifestations of the disease. Precedence should be given to methotrexate when selecting an immunosuppressive drug.